(untitled) (Tạp chí Y học Cộng đồng, 2024)
Aims: Stroke is a leading cause of disability worldwide, significantly affecting patients’ ability to perform daily activities. In Vietnam, stroke survivors often face prolonged dependence on others for daily care. This study aimed to describe the clinical characteristics and assess the level of dependence in daily activities among stroke patients at Ha Tinh Rehabilitation Hospital. Methods: A descriptive cross-sectional study was conducted on 117 stroke patients undergoing rehabilitation at Ha Tinh Rehabilitation Hospital from March to September 2024. Patients were assessed using the Barthel Index, which measures independence in 10 basic activities of daily living. Data were collected through medical record reviews, patient observations, and interviews. Statistical analysis was performed using SPSS 25.0, with chi-square tests for differences between proportions. Results: The average Barthel Index score was 50.44 ± 32.42, indicating moderate dependence. Only 16.2% of patients were fully independent, while 49.6% were completely dependent. Factors such as age, educational level, social support, smoking, and clinical conditions like aphasia and dysphagia were significantly associated with levels of independence (p < 0.05). Conclusion: The majority of stroke patients at Ha Tinh Rehabilitation Hospital demonstrated a high level of dependence in daily activities. Interventions targeting social support, lifestyle changes, and early rehabilitation may enhance patient independence and improve outcomes.